2016
DOI: 10.1016/j.stem.2016.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of the SWI/SNF Component Arid1a Promotes Mammalian Regeneration

Abstract: SUMMARY Mammals have partially lost the extensive regenerative capabilities of some vertebrates, possibly as a result of chromatin-remodeling mechanisms that enforce terminal differentiation. Here, we show that deleting the SWI/SNF component Arid1a substantially improves mammalian regeneration. Arid1a expression is suppressed in regenerating tissues, and genetic deletion of Arid1a increases tissue repair following an array of injuries. Arid1a deficiency in the liver increases proliferation, reduces tissue dama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
124
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(138 citation statements)
references
References 49 publications
13
124
1
Order By: Relevance
“…An attractive hypothesis is that NOR-bound sites represent labile/unstable nucleosomes that could hallmark enhancer binding by pioneer TFs. We performed the same analysis with the C/EBPa TF in hepatocytes 19 and found similar results. When examining H2A.Z levels at FoxA2 and C/EBPa sites, we also found more H2A.Z at NORbound sites but unlike for Ets1 and Oct4, only flanking nucleosomes were marked.…”
Section: Resultssupporting
confidence: 59%
“…An attractive hypothesis is that NOR-bound sites represent labile/unstable nucleosomes that could hallmark enhancer binding by pioneer TFs. We performed the same analysis with the C/EBPa TF in hepatocytes 19 and found similar results. When examining H2A.Z levels at FoxA2 and C/EBPa sites, we also found more H2A.Z at NORbound sites but unlike for Ets1 and Oct4, only flanking nucleosomes were marked.…”
Section: Resultssupporting
confidence: 59%
“…However, a recent study showed that loss of Arid1a, a component of the chromatin remodelling complexes SWI/SNF, resulted in improved liver regeneration after partial hepatectomy in mice. 82 Conditional overexpression of Arid1a reduced proliferation in wild type (WT) animals after chemical injury. The molecular mechanisms underlying Arid1a-mediated impaired regeneration involve chromatin remodelling, ultimately altering transcriptional access by C/EBPα and E2F4, transcription factors that support terminal differentiation and antagonise proliferation.…”
Section: Epigenetics and Liver Fibrosismentioning
confidence: 99%
“…Sun et al (1) (Cell Stem Cell, 2016) recently reported that deleting the Arid1a gene in mice greatly enhances the ability to regenerate the liver and ears after induced injury. Arid1a forms part of SWI/ SNF chromatin-remodeling complexes, which normally support promoter access for transcription factors that promote differentiation and inhibit proliferation.…”
mentioning
confidence: 99%
“…Conversely, Arid1a overexpression impaired proliferation and liver regeneration. In addition, inducible whole-body Arid1a deletion is shown to enhance wound healing after ear punching, indicating a more general benefit of Arid1a loss in tissue regeneration (1).…”
mentioning
confidence: 99%